State Youth Policy: Peculiarities of Implementation and Reflection in the State Programs of the Russian Federation and Moscow City - O. N. Lyubina (Управление)
The article considers the essence of the state youth policy and the directions of its implementation at the level of the Russian Federation and Moscow city. The analysis of government programs is made from a position of reflection in them of youth policy events. The necessity of common approaches development to the legal regulation of the state youth policy in the Russian Federation and its subjects is expressed.